The urgent need for newer drugs in routine HIV treatment in Africa: the case of Ghana - Appiedu-Addo, Sekyibea Nana Ama; Appeaning, Mark; Magomere, Edwin; Ansa, Gloria Akosua; Bonney, Evelyn Yayra; Quashie, Peter Kojo (Frontiers in Epidemiology, 2025)
Antiretroviral therapy (ART) has tremendously improved the quality of life of people living with HIV (PLWH). Through rigorous scientific research and development, newer, more effective, and less toxic antiretrovirals (ARVs) have been developed and are available to PLWH in high-income countries (HICs). Although Africa accounts for more than two-thirds of the global burden of HIV/AIDS, this large population does not readily have access to these newer and more effective ARVs. In some instances, new ARVs become available to PLWH in Africa over a decade after they have been approved for use by the Food and Drug Authorities (FDAs) in HICs. Since 2010, 35 new drug entities have been approved; of those, only 3 are in common use in Ghana and most of Sub-Saharan Africa. To achieve the 2030 goal of ending HIV/AIDS as a global health epidemic, it is critical to ensure equity in access to newer and effective ARVs across all regions, including Africa, where the majority of PLWH reside. We highlight here the urgent need to make newer ARVs available in Africa to ensure the realization of the Global End AIDS by 2030 goal.